Neanderthal logistic mobility during MIS3: Zooarchaeological perspective of Abric Romaní level P (Spain). (1st December 2019) - Marín, Juan; Rodríguez-Hidalgo, Antonio; Vallverdú, Josep; Gómez de Soler, Bruno; Rivals, Florent; Rabuñal, José Ramón; Pineda, Antonio; Chacón, María Gema; Carbonell, Eudald; Saladié, Palmira
Abstract: Mobility strategies of Neanderthal groups are studied through the characterization and analysis of archaeological sites and traditionally compared to the types of settlements present-day hunter-gatherer groups, based on their mobility strategies. The faunal record of level P of Abric Romaní is a unique source of information for analysing the foraging behaviour developed by Neanderthals during MIS3. The assemblage is divided into two separate and well-defined sublevels: Pa and Pb. Through the taphonomic study of the remains and their spatial distribution, it was possible to define the characteristics of these human occupations. The analyses indicate that the assemblage was the result of at least two different types of occupations: 1) A transitory residential camp during short halts, focusing on the exploitation of red deer; 2) A hunting camp/intermediate butchering site for the specialized capture of horses. The presence of occupations focusing on the supply of specific resources is typical of collector groups. The results of the zooarchaeological study of level P characterize the Neanderthals of Abric Romaní as groups involved in a logistic mobility system, who moved throughout the territory depending on the availability of large ungulates. Highlights: Abric Romaní level P was the result of at least two different types of occupations. Transitory residential camp during short halts for the capture of red deer. Hunting camp/intermediate butchering site for the specialized capture of horses. Neanderthals were involved in a logistic mobility system.